Sounding out the Silence of Gregor Samsa: Kafka's Rhetoric of Dys-Communication - Robert Weninger (Studies in 20th & 21st Century Literature, 1993)
Through his transformation, Gregor Samsa, rather than simply silencing himself, allows his repressed voice to be heard palimpsestically in the language of his family and the boarders. His story is one of inverted—rather than aborted—communication. An analogous inversion governs the relationship between Kafka and his father and Kafka and his interpreters. As a child, Kafka could make little sense of his father's rules and his contradictory actions; later, he reduplicates in his writings this grammar of "dys-communication." Our puzzled and often frustrated reactions to Kafka's texts can therefore be seen to mirror his equally puzzled and frustrated reactions to his father's discourse. Thus a comparison of the basic situation of communication displayed in Kafka's "Letter to his Father," "The Metamorphosis," and Kafka-scholarship discloses a symmetry of responses behind the child's perspective, the Samsas' tale, and our quest for meaning.
Keywords: Gregor Samsa; palimpsestically; silence; language; boarder; inverted communication; communication; analogous inversion; Kafka; father; relationship; interpreter; rules; child; dys-communication; mirror; frustrated; puzzle; puzzled; Letter to his Father; The Metamorphosis; Kafka-scholarship; symmetry; Samsas; meaning